FORMULATION OF GEL MASK MASK- Off EXTRACT ARABIKA COFFEE LEAF ETANOL (Coffea Arabica) AS ANTI- AGING - Sihombing, Juliana (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Arabica coffee leaves (coffea Arabica L.) are known to contain flavonoids which have antioxidant activity. This study aims to find out whether arabica coffee leaf extract can be formulated in the form of anti-meat pell-off gel mask preparations. The gel dosage formula is made by comparing the concentration of arabica coffee leaf ethanol extract with formulas 1%, 3% and 5% . The gel that is formed is tested for physical properties and stability. viscosity value of viscosity of 7500-27050cps, spread power of 5-.7.5 cm. Pell-off mask preparation for homogeneous produced arabica coffee leaf ethanol extract, PH 5.1-6.1 stable in 4 weeks storage, non-irritating to the skin and long drying 22-30 minutes, Arabica coffee leaf ethanol pell-off gel mask provides better anti-aging effectiveness for 4 weeks compared to blank. The F3 pell-off gel mask (5%) provides a better anti-aging effect than other formulas.